Practical Procedures in Orthopaedic Surgery Joint Aspiration/Injection, Bone Graft Harvesting and Lower Limb Amputations - Giannoudis, Peter V. (Springer London : Imprint: Springer, 2012)
Practical Procedures in Orthopaedic Surgery will be an essential guide for surgeons in training, providing step by step approaches to performing Joint Aspiration/Injection, Bone Graft Harvesting and Lower Limb Amputations. Practical guidance will be given on Indications- Preoperative assessment, positioning and preparing the patient, approach required, tips and tricks, closure, postoperative complications, protocol of mobilization and follow-up procedure. All the procedures performed will include numerous intraoperative photographs and illustrations.